Electron-electron drag in crystals with a multi-valley band. Magnetoresistivity and Hall-effect - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Hall-effect and magnetoresistivity of electrons in multi-valley bands of Si and
Ge is considered with due regard for direct intervalley drag. Search of contribution of
this drag shows that this interactioin sufficiently changes both effects. Calculated here
values substantially differ from consequent those obtained on the base of popular -
approximation.